RASIONALITAS PENETAPAN PIDANA TAMBAHAN DALAM PENANGGULANGAN KEJAHATAN KORPORASI DI BIDANG NARKOBA - Sujasmin, Sujasmin (Sekolah Tinggi Hukum Bandung, 2010)
Act No. 5 of 1997 on psychotropic and Act No. 35 of 2009 on narcotic have already regulated corporations as subjects of criminal act, in addition to the sentence to the people. Nevertheless, there are still shortcomings particularly in stipulation of additional sentence to corporations which have committed criminal acts against Act No. 5 of 1997 and Act No. 35 of 2009. The problem formulations are as follow: the first; how is the rationality of additional sentence stipulation in prevention of corporate crime in narcotic and psychotropic fields?. The second; how are the material and formalÂ consequences against additional sentence stipulation in prevention of corporate crime in narcotic and psychotropic fields?Keywords: Rationality â Stipulation Â Corporate Crime Â Additional Sentence